Differentiation of early gastric cancer infiltration depths using nonlinear optical microscopy. (13th July 2021) - Xu, Xueqin; Wang, Guangxing; Peng, Dongqing; Zheng, Liqin; Lin, Lisheng; Zheng, Xiaoling; Zhan, Zhenlin; Zhuo, Shuangmu
Abstract: Gastric cancer, one of the most common malignant tumors that can affect the digestive system, poses a serious threat to human life. The survival rate of gastric cancer patients depends on early detection and treatment. The widespread adoption of endoscopy has improved the detection rate of early gastric cancer. Accurate preoperative diagnosis of early gastric cancer is key to developing individualized treatment strategies. Here, nonlinear optical microscopy (NLOM) is used to differentiate between normal gastric mucosae and those with early gastric cancer. Furthermore, the quantitative relationship between submucosal infiltration depth and collagen signals in early gastric cancer is explored. First, the two-dimensional collagen direction angle was measured as an indicator to identify cancerous tissue. The orientation indexes of collagen fibers in normal and cancerous tissues were found to be 0.8511 ± 0.0839 and 0.6466 ± 0.07429 ( P < 0.0001), respectively, indicating a significant decrease for the cancerous site. The backscattered second harmonic generation (SHG) signal corresponding to the collagen content and the three-dimensional collagen fiber orientation were then studied for early gastric cancer at different infiltration depths. The backscattered collagen SHG signal (a.u.) in the infiltrated lamina propria, muscularis mucosa, and submucosa were found to be 0.1850 ± 0.0393, 0.0870 ± 0.0189, and 0.0435 ± 0.0163, respectively. The 3D directional variance of collagen corresponding to the three infiltration depth sites were 0.6108 ± 0.0707, 0.6794 ± 0.0610, and 0.8200 ± 0.0618 ( P < 0.05), respectively. Significant differences between the early gastric cancer collagen signals at different infiltration depths were observed. Our results indicate that NLOM can differentiate cancerous tissue from normal tissue, and thus diagnose early gastric cancer based on infiltration depth. NLOM provides a new evaluation method for the real-time in situ diagnosis of early gastric cancer and has important clinical significance for preparing accurate individualized treatment guidance.